Digital transformation of the public finance system: challenges, inclusivity, and prospects for sustainable development - Bulavynets, Oleksandr; Булавинець, О.; Shashkevych, Oleksandr; Шашкевич, О.; Gerchakivskіy, Sviatoslav; Герчаківський, С.; Gavkalova, Nataliia; Гавкалова, Н.; Atamas, Oleksandr; Атамас, Олександр Петрович (Technology and Education of the Amazon (ITEGAM), 2026)
The study aims to analyze the digitalization of Ukraine’s public finance system during 2022–2025 in the context of critical challenges, financial inclusion, and sustainable development under martial law. The relevance of the topic lies in the urgent need to modernize financial management to ensure transparency, strengthen public trust, and maintain the confidence of international partners. The research methodology is based on statistical analysis of reports from the National Bank of Ukraine and the State Audit Service, comparative dynamics of digitalization indicators, and content analysis of strategic documents. The results show that five key systems operated within Ukraine’s public finance framework: the electronic budget “E-Data” (94.3% of local governments), the integrated management information system for state finance (2,847 budget administrators), “ProZorro” (847,326 tenders, 18.3 million users), and the automated tax administration system “Diia” (98.7% of electronic declarations). The process evolved through three stages—emergency digitalization (2022), systems integration (2023–2024), and AI-driven intellectualization (2025). Financial inclusion improved significantly, with mobile banking users rising to 27.8 million, cashless payments reaching 84.6%,and e-state payments 97.3%. Sustainable development was supported by the growth of green bonds and procurement, while major issues included low digital skills, weak financial control automation, and rural-urban disparities, requiring targeted national programs Метою дослідження є аналіз цифровізації системи державних фінансів України протягом 2022–2025 років у контексті критичних викликів, фінансової інклюзії та сталого розвитку в умовах воєнного стану. Актуальність теми полягає в нагальній потребі модернізації фінансового управління для забезпечення прозорості, зміцнення довіри громадськості та підтримки впевненості міжнародних партнерів. Методологія дослідження базується на статистичному аналізі звітів Національного банку України та Державної аудиторської служби, порівняльній динаміці показників цифровізації та контент-аналізі стратегічних документів. Результати показують, що в рамках державних фінансів України функціонувало п'ять ключових систем: електронний бюджет «E-Data» (94,3% місцевих органів влади), інтегрована інформаційна система управління державними фінансами (2847 розпорядників бюджету), «ProZorro» (847 326 тендерів, 18,3 мільйона користувачів) та автоматизована система адміністрування податків «Дія» (98,7% електронних декларацій). Процес розвивався у три етапи: екстрена цифровізація (2022), системна інтеграція (2023–2024) та інтелектуалізація на основі штучного інтелекту (2025). Фінансова інклюзія значно покращилася: кількість користувачів мобільного банкінгу зросла до 27,8 мільйона, безготівкові платежі досягли 84,6%, а електронні державні платежі – 97,3%. Сталий розвиток підтримувався зростанням зелених облігацій та закупівель, тоді як основними проблемами були низький рівень цифрових навичок, слабка автоматизація фінансового контролю та нерівність між сільською та міською місцевістю, що вимагало цілеспрямованих національних програм.
Цифрова трансформація системи державних фінансів: виклики, інклюзивність та перспективи сталого розвитку
Keywords: public finances; державні фінанси; digitalization; цифровізація; financial inclusion; фінансова інклюзія